Formulasi dan Uji Stabilitas Fisik Sediaan Essence dari Ekstrak Etanol 96% Daun Bayam Merah (Amaranthus Tricolor L.) Sebagai Perawatan Kulit Wajah: Formulation and Physical Stability Tests of Essence from 96% Ethanol Extract of Red Spinach (Amaranthus Tricolor L.) Leaf as Facial Skin Treatment - Fidya Mulya Asanah; Linda Suryanti; Leli Nurlaeli (UIMA Press, 2023)
Essence is a skin care product that is part of skincare. It is water-based and works to moisturize, protect and promote overall skin health. Red spinach leaves (Amaranthus Tricolor L.) is a plant that contains high antioxidants, which can be used as skin care products. The purpose of this study was to carry out the formulation and physical stability test of essence preparations using the cycling test method. This study used an experimental method, namely the extract was obtained using the maceration method, then formulated into an essence preparation consisting of PEG-40 hydrogenated castor oil, butylene glycol, glycerin, xanthan gum, methyl paraben, 96% ethanol, distilled water, and the addition of spinach leaf extract. red with concentrations of F1(0.5%), F2(0.9%), F3(1.3%) respectively. As a blank (F0) for essence preparations without the addition of extracts. 96% ethanol extract of red spinach leaves (Amaranthus Tricolor L.) can be formulated into essence products with concentrations of 0.5%, 0.9% and 1.3%. Stability testing using the accelerated method/cycling test on essence products showed stable results, because there was no change in odor, color and dosage form. The best formulation is formulation 3 with an active substance concentration of 1.3% where the pH value is 5.9 and the viscosity value is 270 mPa.S. these results meet the range of pH requirements needed by facial skin where a good pH requirement for facial skin is 4.5-6 and also meets the standard essence viscosity requirements, namely 230-1150 cPs (230-1150 m.Pa.S).